Effectiveness of Cold Compress and Lavender Aromatherapy on Reduction in Postpartum Perineal Pain Intensity - Yuanita Syaiful; Lilis Fatmawati; Siti Nur Qomariah; Aidatur Runis (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2020)
Introduction: Every postpartum mother got a perineal wound and experience pain. This pain results in unpleasant effect such as fear of movement which can lead to problems such as sub uterine involution, unhealthy release of lochea, and postpartum bleeding. The purpose of the study was to determine effectiveness of cold compress and lavender aromatherapy on the reduction in postpartum perineal pain intensity. Methods: This study uses a Quasi-Experiment method with a pre-post test design. 32 samples were divided into 16 cold compresses and 16 lavender aromatherapy. The independent variable is the supply of cold compresses and lavender aromatherapy. The dependent variable is postpartum perineal pain. Data collection with standard operating procedures (SOP) for cold compresses, and lavender aromatherapy and observation sheets with bourbonic pain scales. Analyzed using the Wilcoxon test to find out before and after, to determine the effectiveness of using the Mann Whitney test. Results : Wilcoxon Signed Rank Test P=0.000 which means there is a difference in pain intensity before and after cold compresses are given, As for the lavender aromatherapy variable, the value of P=0.008 means that there is a difference in pain intensity before and after lavender aromatherapy is given. Mann-Whitney U Test statistic shows that the significance value P = 0.077, so there is no significant difference between giving cold compress and lavender aromatherapy to reduction in postpartum perineal pain intensity. Conclusions: Cold compresses and lavender aromatherapy can be used as nonpharmacological therapy in reducing the intensity of postpartum perineal pain.